PENINGKATAN MODEL PROJECT BASED LEARNING BERBASIS PENDEKATAN CULTURALLY RESPONSIVE TEACHING DAN MEDIA FLIPBOOK CERITA TOKOH PAHLAWAN TERHADAP KEMAMPUAN MENULIS TEKS PIDATO PESERTA DIDIK DI SEKOLAH DASAR - Feby Inggriyani; Sarah Anida Putri (Literasi: Jurnal Ilmiah Pendidikan Bahasa, Sastra Indonesia dan Daerah, 2026)
The purpose of this study is to ascertain if the Heroic Figures Story flipbook medium and the Project-Based Learning model, which is based on the Culturally Responsive Teaching approach, have improved fifth-grade elementary school students' capacity to produce spoken texts. A quasi-experimental and nonequivalent control group design is the technique employed. Fifth-grade primary school students from classes V-B and V-C, each with 33 pupils, participated in the study. Purposive sampling was the method used in this investigation. In this study, tests and observations were used as data-gathering methods. A speech text writing ability exam was one of the tools utilised. IBM SPSS Statistics 2.6 software was utilised for the hypothesis test data analysis method, specifically the n-gain test. According to the study's findings, students at SDN 024 Coblong who received instruction using the PjBL model based on the CRT approach and the Heroic Figures Story Flipbook medium saw a more notable improvement in their ability to produce speech texts. This is demonstrated by the n-gain calculation findings, which show that the experimental class is in the medium group with a gain index of 0.55 (or an increase of 55.46%). In contrast, the control group only attained a modest gain index of 0.05 (5.20%). This indicates that the experimental class's writing proficiency increased significantly more than that of the control group. Thus, it can be said that the use of the PjBL model, which is based on the CRT approach and Flipbook media, is deserving of being suggested as an alternate teaching strategy to enhance primary school students' speech writing abilities.